1999
DOI: 10.1021/jo990364d
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Intramolecular Ring Cyclization of Protonated and BF3-Coordinated trans- and cis-4,5-Epoxyhexan-1-ol

Abstract: The potential energy surface for the rearrangement of cis- and trans-4,5-epoxyhexan-1-ol with acid and the Lewis acid BF(3) to five- and six-membered cyclic ethers has been investigated by ab initio methods. The transition structures involving both inversion and retention of configuration at the reaction center at the HF/6-31G and B3LYP/6-31G levels are characterized. The preference for furan formation over pyran is attributed to the more favorable O-C(ep)-O bond angles at the transition structures for furan f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…Coxon et al recently reported an ab initio study of the intramolecular ring cyclization of protonated and BF 3 ‐coordinated cis ‐4,5‐epoxyhexan‐1‐ol 25. The potential energy surface for the rearrangement of protonated epoxy alcohols shows activation barriers much more favorable to five‐membered transition structures leading to furan.…”
Section: Resultsmentioning
confidence: 99%
“…Coxon et al recently reported an ab initio study of the intramolecular ring cyclization of protonated and BF 3 ‐coordinated cis ‐4,5‐epoxyhexan‐1‐ol 25. The potential energy surface for the rearrangement of protonated epoxy alcohols shows activation barriers much more favorable to five‐membered transition structures leading to furan.…”
Section: Resultsmentioning
confidence: 99%
“…[25] The potential energy surface for the rearrangement of protonated epoxy alcohols shows activation barriers much more favorable to five-membered transition structures leading to furan. [25] The potential energy surface for the rearrangement of protonated epoxy alcohols shows activation barriers much more favorable to five-membered transition structures leading to furan.…”
Section: Mukaiyama Aldol Reactionsmentioning
confidence: 99%
“…3). This structural change in turn alters the trajectory of the nucleophile toward the epoxide electrophile, a factor that computations suggest is most important for selectivity in epoxide-opening reactions (27,28). Because the template of 1b cannot participate in similar hydrogen-bonding interactions, an unselective reaction proceeds with the template in the more stable chair conformation.…”
Section: Resultsmentioning
confidence: 99%